Comparative Study of Cycle Threshold RT-PCR SARS Cov-2 between Saliva Specimen and Nasopharyngeal Swab - Citraningtyas Indriana; Tjie Kok (Universitas Gadjah Mada, 2023)
Coronavirus Disease 2019 (Covid-19) is an infectious disease that spreads quickly and attacks respiratory system that can cause death. The main diagnosis of Covid-19 is conducted by nasopharyngeal swab, an invasive method which can in turn increase the risk of transmission from patient to swabber. Hence, there is a need for non-invasive methods development, one of which is using saliva specimen. This study aims to evaluate the potential of using saliva specimen for diagnosis as an alternative of nasopharyngeal swab. The study was conducted on confirmed patients at Hajj Dormitory Embarcation Surabaya. The samples were collected randomly form 35 patients at Hajj Dormitory Embarcation Surabaya and evaluated at Surabaya Regional Health Laboratory. The results showed that there was no significant difference between cycle threshold RT-PCR of nasopharyngeal swab and saliva specimen. The sensitivity and specificity of saliva specimen are 88.2% and 100%, respectively, of nasopharyngeal swab. Hence, saliva specimen has the potential to be used as an non-invasive method for Covid-19 diagnosis.